Pengaruh Parameter Faktor Stir Casting pada Porositas KOmposit Al-SiC - Sadi Sadi; Viktor Malau; M Waziz Wildan; Suyitno Suyitno (ROTOR, 2014)
This research aims to analyze the effect of stir casting factor parameters on  Al-SiC composite porosity using Taguchi method.   Composite materials used aluminum alloy   Al-Si as matrix and SiC particle (silicon carbide) sized -400 mesh as reinforcement.   Al-SiC composites specimen porosity was tested using  Archimedes  principles.  Experimental  design  using  L16  orthogonal  arrays  Taguchi method standard. Factors used  for  the experiment were SiC content, melt  temperature, rotation speed and stirring  time  duration,  each  using  4  variation.  Experimental  results  showed  that  increasing  SiC content parameters and stirring rotation speed from 100 into 300 rpm can increase Al-SiC composite oporosity,  but  increasing melt  temperature  above  700 C  and  stirring  time  from  10-30 minutes  candecrease the porosity. The most significant factor affecting Al-SiC composite porosity was SiC conten with 84,7 % contribution. Microstructures of Al-SiC casting composites were observed using scanning electron microscopy  (SEM). Keywords: Al-SiC composites, porosity,  stir casting, experimental design, taguchi method